2013
DOI: 10.1177/1075547012470707
|View full text |Cite
|
Sign up to set email alerts
|

Framing Synthetic Biology

Abstract: Under what conditions does the perceived "unnaturalness" of a specific application of synthetic biology influence its public acceptability? Using data from a framing experiment embedded in a national survey of Canadian adults, we argue that this consideration leads to negative perceptions of the technology only when opponents of the application use rhetoric that refers to its unnaturalness and when characteristics of the application itself, such as the use of genetic material from "dissimilar" organisms, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…An additional factor may be the extent to which technologies allow humans to interfere with the natural world (Hansen, ; Sjöberg, ). Researchers have proposed that resistance to scientific and technological developments may arise from discomfort with tampering with nature, and that some people experience this discomfort more than others (Corner, Parkhill, Pidgeon, & Vaughan, ; Dragojlovic & Einsiedel, ; Vandermoere, Blanchemanche, Bieberstein, Marette, & Roosen, ; Wolske, Raimi, Campbell‐Arvai, & Hart, ).…”
Section: Introductionmentioning
confidence: 99%
“…An additional factor may be the extent to which technologies allow humans to interfere with the natural world (Hansen, ; Sjöberg, ). Researchers have proposed that resistance to scientific and technological developments may arise from discomfort with tampering with nature, and that some people experience this discomfort more than others (Corner, Parkhill, Pidgeon, & Vaughan, ; Dragojlovic & Einsiedel, ; Vandermoere, Blanchemanche, Bieberstein, Marette, & Roosen, ; Wolske, Raimi, Campbell‐Arvai, & Hart, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers have been found to be sceptical about the new biotechnologies used in food production, and reluctant to eat meat from vaccinated animals (Scudamore, 2007;Zingg & Siegrist, 2012). There is a limited literature on understandings of synthetic biology applications, but earlier studies have found that people consider synthetic biology to be risky because they regard it as a form of human interference with nature, and that people's attitudes to applications of synthetic biology depend on the degree to which the applications are seen as 'natural' (Avellaneda & Hagen, 2016;Dragojlovic & Einsiedel, 2013). 'Naturalness' is perceived to be a sign of safety and order, whereas 'unnaturalness' signals potential danger to many consumers and rises anxiety (Ditlevsen & Andersen, 2020;Douglas, 2002).…”
Section: Synthetic Biology and Riskmentioning
confidence: 99%
“…Nature's comic also invited readers to consider the implications of constructing life. Among them, it may have elicited the notion of risks posed by deliberately tinkering with nature, which is one of the most prevalent associations found in surveys and focus group work involving lay people (Dragojlovic and Einsiedel 2013a). It is arguable, though, whether this comic contributed to a positive perception of SB as obviously intended or, instead, to a notion of hazard and uncontrollability, and of the average SB scientist being a kind of doctor Frankenstein (Gschmeidler and Seiringer 2012).…”
Section: Introductionmentioning
confidence: 99%